Adsorption of Gas-Phase Cyclohexanone on Atmospheric Water Films - Shangpeng Hao; Chao Sun; Yuanpeng Zhang; Haitao Wang; Wenbo Zhao; Xiaolu Wang; Jinghai Li (Atmosphere, 2021)
The fate of atmospheric volatile organic compounds (VOCs) strongly depends on the partitioning processes on the surface of aerosols, which are coated with a thin water film. However, the behavior of VOCs in the aqueous film of aerosols is difficult to measure. In this work, the interfacial partition constant of cyclohexanone was determined using a novel flow-tube reactor. A thin, aqueous film placed in the reactor was exposed to cyclohexanone gas. The subsequent partitioning was measured using chromatography techniques. The quality control tests were first conducted to ensure the accuracy of the adsorption experiments. The cyclohexanone concentration was then plotted as a function of film thickness to obtain the partitioning constants. As the thickness of the water film decreased, the aqueous concentration of cyclohexanone increased, indicating that surface adsorption played a dominant role in the uptake of cyclohexanone. According to the temperature dependence of the interfacial partition constant, the solvation enthalpy and entropy of cyclohexanone were obtained. The results of this study would help to elucidate the effect of atmospheric water film on the gas–aerosol partitioning of VOCs, and thus can help to better understand the fate of VOCs in the atmosphere.